Optimization of the technique for manufacturing the osteoplastic material based on type 1 human collagen and allogeneic bone chips - A. A. Ofitserov; M. S. Makarov; M. V. Storozheva; N. V. Borovkova; I. N. Ponomarev (Трансплантология (Москва), 2023)
Introduction. Biological grafts, including bone chips and collagen, are supposed to be promising in the treatment of bone tissue treatment. Nevertheless, manufacturing of these grafts still needs to be standardized. Aim. To optimize methodology of osteoplastic material production, based on allogenic 1 type collagen and bone chips. Material and methods. Osteoplastic material grafts were produced, using with allogeneic bone chips 180-800 µm and type 1 collagen solution in acidic acid. We studied total integrity of graft, collagen quality, morphofunctional properties of line M-22 human cells interacting with different type of osteoplastic material grafts. Results. Procedures for manufacturing the osteoplastic material did not significantly affect the quality of collagen in its composition, while lyophilized grafts had pronounced acidogenic and toxic effects in cell culture. Soaking osteoplastic material in isotonic solution for 30 min or longer increased its biocompatibility in vitro. Adhesion properties of osteoplastic material widely varied depending on collagen concentration and bone chips size. Conclusion. Osteoplastic material prepared with allogeneic bone chips of 180–800 µm and collagen solution in acidic acid had pronounced acidogenic and toxic effects in vitro that could be considerably reduced by soaking in isotonic solution. Varying the collagen concentration and the size of bone chips one could produce biocompatible osteoplastic material grafts with high and low adhesion properties.